Examination of the frequency and localization of sigmoid canal with CBCT: A retrospective study - Kaya, Menduh Sercan; Dogan, Mehmet Emin; Kotanli, Sedef (Medicine (Baltimore), 2025)
Recently, a variational canal starting from the sigmoid notch and extending in the ramus has been reported. The aim of this study was not only to investigate the presence and localization of the sigmoid canal (SC) between the sexes, which has not been studied before, but also to define the morphometric characteristics of the SC. The possible complications that this anatomical variation may cause are also being discussed. Between 2022 and 2024, a total of 546 cone beam computed tomography images obtained in sagittal, coronal, and horizontal planes were retrospectively analyzed. The presence, localization, and morphometric characteristics of the SCs were recorded and evaluated using statistical analysis software. The presence of SC was observed in 5.5% of the images and it was determined that 4.0% of these canals were unilateral and 1.5% were bilateral. The rate of right SC was 3.3% and the rate of left SC was 3.7%. When morphometric evaluation is made, the average value of the length of the SC is 8.0 mm, with a minimum value of 3.1 mm and a maximum value of 13.9 mm. Knowledge of the SC will prevent possible complications in surgical procedures, provide a more accurate diagnosis at the diagnostic stage and ensure that the treatment plan is created appropriately. More studies are needed on this subject.